Efficacy of lidocaine spray, either alone or in combination with anti-inflammatory throat spray, in alleviating discomfort during unsedated esophagogastroduodenoscopy: A double-blind randomized controlled trial - Buranathawornsom, Arunluk; Bunchorntavakul, Chalermrat (Journal of Medicine and Health Sciences, 2025)
Controlling patients’ pain during Esophagogastroduodenoscopy (EGD) is a fundamental factor in increasing patient satisfaction, reducing discomfort, and improving patient cooperation. Although lidocaine spray is a common and safe anesthetic option for unsedated EGD, endoscopists continue to seek ways to improve the preparation process before the EGD procedure. This study aimed to compare patient satisfaction, pain, and discomfort between the use of lidocaine spray alone and in combination with anti-inflammatory throat spray. This prospective, randomized clinical trial was conducted at Yala Hospital, Yala, Thailand between January 2024 and May 2024. Patients were randomly assigned to one of two groups: one received only a lidocaine spray (Group A), while the other received a combination of lidocaine spray and an anti-inflammatory throat spray (Group B, using Benzydamine Hydrochloride). After the procedure, patients rated their satisfaction, pain, and discomfort on a numerical scale from 0 to 10. A total of 100 subjects were randomized to receive either Lidocaine Spray alone (n=50) or a combination of Lidocaine Spray and an Anti-inflammatory Throat spray (n=50). The patient satisfaction score (Group A: median (IQR) 10 (9,10); Group B: median (IQR) 9 (9,10); p=0.248), pain score (Group A: median (IQR) 3 (1,5); Group B: median (IQR) 2.5 (0,5); p=0.624) and discomfort score (Group A: median (IQR) 3 (1,5); Group B: median (IQR) 3 (2,5); p=0.203) were not significantly different between the groups. Adverse events, including sore throat, bitter taste, nausea, and vomiting, were lower in group B, though the differences were not statistically significant. This study concludes that both methods have similar effects on patient satisfaction, pain and discomfort. Therefore, preparation for EGD using lidocaine spray alone remains a safe and effective approach to local anesthesia. Adding an anti-inflammatory throat spray may be an option to help reduce certain adverse events.